Family history in breast cancer in São Luís, Maranhão, Brazil. (December 2016) - Ribeiro, Maria; Silva, Marcos; Muniz Filho, Walbert Edson; Nascimento, Anna; Souza, Rodrigo; Machado, Carlos; Silva, Dulcelena; Barros Bezerra, Geusa; Castro Viana, Graça; Soares Brandão Nascimento, Maria do Desterro
Abstract Background Familial cancer includes some types of cancer aggregation without a well-defined inheritance pattern. Cancer genetics is an essential component of clinical practice in oncology. In Brazil, breast cancer is the leading cause of death in women. In Maranhão, studies on genetic predisposition are necessary to investigate the incidence and mortality rates. The aim of this study was to investigate familial cancer among relatives of women who died of breast cancer in São Luís, Brazil, constructing a pedigree to identify families with a hereditary predisposition, an important step in the early diagnosis of malignant tumors. Methods The city of São Luís is located on the Island of Maranhão, northeastern Brazil, with a population of 997, 098 inhabitants mainly comprising blacks and mulattoes, including descendants of runaway slaves from the Amazon region itself. Data for pedigree construction were obtained from the records of 54 patients seen at the Aldenora Bello Institute of Oncology, São Luís, between 2000 and 2007, as well as by interview with relatives of the patients. Results The mean patient age at diagnosis was 39.5 years. Most women were mulattoes (36/54, 66.6 %). A history of cancer was observed in 18 families, with 16 families possessing cases of cancer among first-degree relatives and five among second-degree relatives. Conclusion A concentration of cancer cases was found in families of patients diagnosed until the age of 40, a finding demonstrating the importance of a family history prior to genetic counseling.